Impact Of Using Modern Technology In The Field Of Emergency Medicine In Health Facilities In Saudi Arabia (The Review of Diabetic Studies, 2024)
Saudi Arabia has heavily invested in healthcare technology in line with the vision 2030, there is a big gap in the awareness of the actual effects of this technology on emergency departments (EDs). The research evaluated the application and the success of contemporary technologies, such as Electronic Health Records, telemedicine, and point-of-care testing, in Saudi EDs. It was a cross-sectional survey of 350 healthcare professionals working in major hospitals in Riyadh and Makkah. Data analysis was done using descriptive statistics, ANOVA, t-tests and regression modeling. In the study, the overall score of technology adoption was moderate (68.5/100), with a positive correlation, though, strongly positive between technology adoption and workflow efficiency (r=0.612, p